Intravenous but not intragastric urogastrone-EGF is trophic to the intestine of parenterally fed rats. Issue 5 (May 1987) - Goodlad, R A; Wilson, T J; Lenton, W; Gregory, H; McCullagh, K G; Wright, N A
Abstract : The effects of beta-urogastrone/human epidermal growth factor (URO-EGF) on intestinal epithelial cell proliferation were studied in rats in which intestinal cell proliferation had been reduced to a steady state basal level, by maintaining the rats on total parenteral nutrition. The accumulation of arrested metaphases over a two hour time period was determined in a dose response study. Increasing doses of URO-EGF progressively raised the two hour collection of metaphases and intestinal weights. Intravenous infusion of URO-EGF was also effective in restoring cell proliferation when it was infused after the intestine had become hypoproliferative. beta-urogastrone/human epidermal growth factor administered through an intragastric cannulae thrice daily had no significant effect on intestinal weight or crypt cell production rate or metaphase collection. It is proposed that one of the in vivo actions of urogastrone-epidermal growth factor is the maintenance of gastrointestinal growth and that this occurs through a systemic rather than a luminal mechanism.